PENGARUH PEMBELAJARAN AKSELERASI DENGAN PENDEKATAN SAVI TERHADAP HASIL BELAJAR TEKNIK SHOOTING BASKET SMPN 1 - Lizara, D. Nency; Simanjuntak, Victor G; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractShooting in a basketball game is one way to generate points. To put the ball into the ring is not just throwing the ball, but also accompanied by repulsion and directing the ball into the basketball hoop. The problem in this research is whether there is influence of SAVI approach to learning result shooting basketball. The purpose of this research is to know the effect of acceleration learning model by using SAVI approach to learning result shooting basketball. The population in this research is 7 class VIII with 224 students. The sampling of this research using purposive sampling technique, by selecting samples from population who got value below KKM 75 that is 45 learners as experiment class. The method used in this research is experiment with pre-experimental design. Data analysis using computer with analysis using t-test. Based on the result of t-test in experimental class, p value 0,000 <0,05 then Ho is rejected (Ha accepted) means that there is influence of acceleration learning model by using SAVI approach to learning result of basketball shooting, with the difference of average value 24.35 . Â Keywords: SAVI, Learning Outcomes, Shooting.